2018
DOI: 10.1007/s12035-018-1082-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Alpha-Synuclein Oligomers Induce Parkin S-Nitrosylation: Relevance to Sporadic Parkinson’s Disease Etiopathology

Abstract: α-Synuclein (ASN) and parkin, a multifunctional E3 ubiquitin ligase, are two proteins that are associated with the pathophysiology of Parkinson's disease (PD). Excessive release of ASN, its oligomerization, aggregation, and deposition in the cytoplasm contribute to neuronal injury and cell death through oxidative-nitrosative stress induction, mitochondrial impairment, and synaptic dysfunction. In contrast, overexpression of parkin provides protection against cellular stresses and prevents dopaminergic neural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 71 publications
0
42
0
Order By: Relevance
“…Moreover, α-Syn and ATP-induced free radicals generation was significantly prevented by pretreatment with nonselective and selective P2X7R antagonists. To verify that the cytosolic redox environment was affected by the increase in ROS, SH-SY5Y cells were transiently transfected with a reporter gene coding for a redox-sensitive green fluorescent protein (roGFP, [27]) and treated with α-Syn for 24 h. The results indicated that α-Syn significantly deregulates cellular redox state in SH-SY5Y cells. Moreover, this effect by α-Syn was significantly ameliorated by PPADS and AZ 11645373 pretreatment (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, α-Syn and ATP-induced free radicals generation was significantly prevented by pretreatment with nonselective and selective P2X7R antagonists. To verify that the cytosolic redox environment was affected by the increase in ROS, SH-SY5Y cells were transiently transfected with a reporter gene coding for a redox-sensitive green fluorescent protein (roGFP, [27]) and treated with α-Syn for 24 h. The results indicated that α-Syn significantly deregulates cellular redox state in SH-SY5Y cells. Moreover, this effect by α-Syn was significantly ameliorated by PPADS and AZ 11645373 pretreatment (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this effect by α-Syn was significantly ameliorated by PPADS and AZ 11645373 pretreatment (Figure 2b). Since the activation of P2X7R induced the increased phosphorylation of oxidative stress-related proteins, it is thus possible that the mechanisms of α-Syn neurotoxicity are related to the enhancement of the reactive oxygen species (ROS) level [27]. In addition, P2X7R activation induces ROS generation in various cells including neurons [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…This relatively easy to manipulate mechanism influences the neuroprotective activity of parkin and the tendency of α-syn to aggregate, thus offering important insights into pathophysiological mechanisms leading to PD and potential therapeutic value. Importantly, α-syn also alters parkin levels and activity (Wilkaniec et al, 2019), potentially creating a cycle of self-fueling pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that α-syn is secreted into the extracellular space, and secretion appears to be a precisely regulated, physiological process (Jęśko et al, 2017). However, in PD, abnormal excess release of monomeric and/or aggregated α-syn might lead to free radical stress (Wilkaniec et al, 2019) and trigger immunological response of surrounding astrocytes and microglia, thereby accelerating the neurotoxic insult (Allen Reish and Standaert, 2015). Moreover, the internalization of secreted α-syn by neurons and glia spreads the neurodegenerative pathology and involves other cell types, including cells that do not typically express significant levels of α-syn (Jęśko et al, 2017).…”
Section: Parkin and α-Syn Secretionmentioning
confidence: 99%
See 1 more Smart Citation